A high-impact polypropylene resin composition and a method for preparing the same
Patent Information
- Application Number
- CN202611336434.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]为此,本发明提供了一种高抗冲聚丙烯树脂组合物及其制备方法,用以解决现有技术中多元增韧体系在聚丙烯基体中协同性差,所导致的抗冲击性差、综合稳定性不足的技术问题
[0015]与现有技术相比,本发明通过PP-g-MAH/纳米二氧化硅母料法预分散解决纳米粒子团聚,通过PP-g-MAH增容构建三相界面桥接结构强化界面粘结并细化EPR相域,通过EPR弹性体与β成核剂双机理实现刚韧平衡与低温抗冲,通过分步密炼分批加料及分段控温挤出确保各组分有序分散与β晶型稳定,最终在保持高刚性的同时实现了优异抗冲性能。
Smart Images

Figure CN122878672A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to a high-impact polypropylene resin composition and its preparation method. Background Technology
[0002] In the automotive parts industry, polypropylene materials face complex and demanding operating conditions. They require excellent low-temperature and room-temperature impact resistance to withstand assembly impacts, everyday bumps, and damage from external impacts in low-temperature environments. Simultaneously, extremely high requirements are placed on the material's structural stability, mechanical stability, and processing stability. This necessitates ensuring stable modulus, tensile properties, and melt flow properties during long-term use to prevent product deformation, cracking, and high defect rates. For example, in automotive dashboard frames and door panel substrates, the industry typically requires a flexural modulus of no less than 2200 MPa to ensure sufficient resistance to deformation and dimensional stability during assembly and long-term use. Currently, conventional multi-component toughening systems in polypropylene modification technologies exhibit poor compatibility and synergy with the polypropylene matrix. Toughening components are prone to uneven dispersion, often resulting in a technical bottleneck where toughening reduces stability, and stability leads to poor impact resistance. This makes it difficult to simultaneously achieve high impact resistance and overall structural and processing stability, failing to meet the stringent requirements of automotive structural components and other demanding applications.
[0003] Therefore, there is an urgent need to develop a high-impact polypropylene resin composition and its preparation method that can achieve synergistic toughening of elastomers, inorganic nanoparticles and β nucleating agents, and whose process is controllable and suitable for industrial production. This is to solve the technical problem that the existing multi-component toughening system has poor synergy in the polypropylene matrix and cannot simultaneously meet the requirements of high impact resistance, high rigidity and high stability. Summary of the Invention
[0004] Therefore, the present invention provides a high-impact polypropylene resin composition and its preparation method to solve the technical problems of poor impact resistance and insufficient overall stability caused by the poor synergy of the multi-component toughening system in the polypropylene matrix in the prior art.
[0005] To achieve the above objectives, the present invention provides a method for preparing a high-impact polypropylene resin composition, comprising the following steps: Step S1: The polypropylene homopolymer and ethylene-propylene rubber (EPR) are dried under preset conditions to obtain pretreated raw materials for later use. Step S2: PP-g-MAH and nano silica are fed into an internal mixer in a preset ratio to obtain PP-g-MAH / nano silica masterbatch. Then, the masterbatch and the polypropylene homopolymer pretreatment raw material are fed into the internal mixer in a preset ratio to control the mass of PP-g-MAH to account for 5%-10% of the total mass of polypropylene homopolymer, and a mixture is obtained. Step S3: The mixture and ethylene-propylene rubber are fed into a mixer in a preset ratio; after mixing for 2 minutes, the β nucleating agent is added in two equal batches with a 30-second interval between the two batches. After mixing for another 3-6 minutes, the antioxidant and lubricant in a preset ratio are added. The mixture is then discharged after 1-2 minutes to obtain the modified mixture. Step S4: The modified mixture is transferred to a twin-screw extruder for melt extrusion granulation, cooled in a water bath, pelletized and dried, and then cooled to room temperature to obtain high-impact polypropylene resin composition granules.
[0006] Furthermore, the preset drying conditions are as follows: polypropylene homopolymer is dried at 80℃-100℃ for 4 hours to achieve a moisture content of ≤0.02%; ethylene-propylene rubber is dried at 60℃-80℃ for 2 hours.
[0007] Furthermore, the mass ratio of PP-g-MAH to nano-silica is 1:0.1-1:0.2; the mixing temperature is 180℃-200℃; the rotor speed is 60rpm-80rpm; and the mixing time is 3min-5min.
[0008] Furthermore, the mass ratio of the masterbatch to the polypropylene homopolymer is 1:10-1:16; the mixing temperature is 190℃-210℃, the rotor speed is 80rpm-100rpm, and the mixing time is 3min-5min.
[0009] Furthermore, the surface of the nano-silica is modified with a silane coupling agent.
[0010] Furthermore, the mixing temperature is 180℃-200℃, and the β-nucleating agent is a TMB-5 type β-nucleating agent or a WBG series β-nucleating agent.
[0011] Furthermore, the antioxidant comprises a compound system of hindered phenolic antioxidants and phosphite antioxidants; the hindered phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the phosphite antioxidant is tris(2,4-di-tert-butylphenyl)phosphite; the mass ratio of the hindered phenolic antioxidant to the phosphite antioxidant is 1:1.5 to 1:2.5.
[0012] Furthermore, based on the total mass of polypropylene homopolymer, ethylene-propylene rubber accounts for 35% of the mass, β-nucleating agent accounts for 0.3% of the mass, antioxidant accounts for 0.7% of the mass, and lubricant accounts for 0.36% of the mass.
[0013] Furthermore, the melt extrusion temperature is controlled in segments: 180℃-190℃ in the feeding section, 210℃-230℃ in the melting section, 230℃-250℃ in the mixing section, 230℃-240℃ in the die head, and 150rpm-250rpm in the screw speed.
[0014] On the other hand, the present invention provides a high-impact polypropylene resin composition, wherein, based on the mass of polypropylene homopolymer, the mass percentage of each raw material component is as follows: The composition consists of 100% polypropylene homopolymer, 35% ethylene-propylene rubber, 0.3% β-nucleating agent, 0.7% compounded antioxidant, 0.36% lubricant, 5%-10% PP-g-MAH, and 0.5%-2.0% nano-silica.
[0015] Compared with existing technologies, this invention solves the agglomeration of nanoparticles through pre-dispersion using PP-g-MAH / nano silica masterbatch, strengthens interfacial bonding and refines the EPR phase domain by constructing a three-phase interface bridging structure through PP-g-MAH compatibilization, achieves a balance between rigidity and toughness and low-temperature impact resistance through the dual mechanism of EPR elastomer and β nucleating agent, and ensures orderly dispersion of each component and stability of the β crystal form through stepwise intensive mixing, batch feeding and segmented temperature-controlled extrusion. Ultimately, it achieves excellent impact resistance while maintaining high rigidity.
[0016] Furthermore, PP-g-MAH preferentially distributes at the EPR / PP interface, forming a bridging structure that significantly enhances interfacial adhesion, enabling the EPR phase domain to effectively transfer stress and dissipate impact energy. TMB-5 induces PP to form a β-crystal structure. β-PP has low lamellar slip resistance, making it prone to lamellar slip and torsion under impact, thus dissipating more energy; moreover, its stress concentration factor is lower than that of α-PP, delaying brittle fracture. MAH groups are anchored to Si-OH on the silica surface, forming hybrid particles uniformly dispersed in the PP matrix. During impact, these particles induce microcracks for toughening, while simultaneously restricting molecular chain relaxation to achieve rigidity enhancement, resulting in a simultaneous improvement in both rigidity and toughness.
[0017] Furthermore, S2 premixing pre-anchors MAH nano-silica to form stable hybrid particles; after adding EPR in S3, the hybrid particles simultaneously bridge PP and EPR, confining the EPR phase domain to 1.2μm, with a β-PP content of 80%. This structure is oriented and fixed during the S4 extrusion process. Temperature control in S4 ensures β-crystal stability, complete PP melting, and no TMB-5 decomposition, with a β-PP content ≥75%. Attached Figure Description
[0018] Figure 1 This is a process flow diagram of the preparation method of the high-impact polypropylene resin composition of the present invention. Detailed Implementation
[0019] To make the objectives and advantages of the present invention clearer, the present invention will be further described below with reference to embodiments; it should be understood that the specific embodiments described herein are merely for explaining the present invention and are not intended to limit the present invention.
[0020] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.
[0021] It should be noted that in the description of this invention, the terms "upper", "lower", "left", "right", "inner", "outer", etc., which indicate directions or positional relationships, are based on the directions or positional relationships shown in the accompanying drawings. This is only for the convenience of description and is not intended to indicate or imply that the device or element must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, it should not be construed as a limitation of this invention.
[0022] Furthermore, it should be noted that, in the description of this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0023] Please see Figure 1 As shown, it is a process flow diagram of the preparation method of a high-impact polypropylene resin composition of the present invention.
[0024] This invention provides a method for preparing a high-impact polypropylene resin composition, comprising the following steps: The function of step S1 is to provide a clean and dry raw material base for subsequent mixing processes through thorough drying. Drying is crucial to prevent hydrolytic degradation of PP during high-temperature mixing, while also ensuring that the EPR elastomer surface is free of moisture and impurities, thus guaranteeing interfacial bonding quality.
[0025] Specifically, the preset drying conditions are as follows: polypropylene homopolymer is dried at 80℃-100℃ for 4 hours to achieve a moisture content of ≤0.02%; ethylene-propylene rubber is dried at 60℃-80℃ for 2 hours.
[0026] Understandably, if the moisture content of PP exceeds 0.02%, during high-temperature mixing at 200℃-250℃, the moisture undergoes a hydrolysis reaction with the terminal hydroxyl groups of the PP molecular chain, leading to a decrease in molecular weight, an increase in molecular weight filtration rate (MFR), and a decrease in impact strength. If EPR is not sufficiently dried, the residual moisture in EPR will generate steam during the mixing process, forming bubble defects. This results in voids within the EPR phase domain, causing stress concentration at these voids during impact and triggering brittle fracture.
[0027] In this embodiment, step S1 includes the following specific steps: Step S11: Take several groups of polypropylene homopolymer, 5 kg per group, and seal them for later use. Seal the ethylene-propylene rubber in the same groups for later use. Spread the polypropylene homopolymer evenly on a stainless steel tray with a thickness of ≤2 cm, and place it in an electric heating drying oven preheated to the set temperature. Dry it for the set drying time, turning the material once every 1 hour during the drying process to ensure uniform heating. In step S12, the ethylene-propylene rubber is dried synchronously under fixed conditions of 60°C and 2 hours. Since the amount of EPR is small and it is only used for subsequent blending, it is not considered as an independent variable in the variable investigation. After cooling, it is sealed and stored.
[0028] Table 1 shows the data on the effect of drying time on moisture content and final impact strength.
[0029] Table 1. Effect of drying time on moisture content and final impact strength
[0030] Table 1 Note: Moisture content was determined using a Karl Fischer moisture analyzer, Mettler Toledo V20, with a detection limit of 0.001%, n=3 batches, and 3 replicates per batch; Impact strength was determined according to GB / T 1843, using a simply supported beam impact testing machine, XJUD-5.5, 5.5 J pendulum, notched specimens, 10 specimens per group, and 3 replicates.
[0031] As shown in Table 1, the moisture content of Example 1-1 after drying decreased to 0.014%, far below the control target of 0.02%, and the impact strength reached 680 J / m, exhibiting both low moisture content and high impact performance. Example 1-2 further reduced the moisture content to 0.012%, with an impact strength of 674 J / m, and all indicators were basically equivalent to Example 1-1. However, when the drying temperature was increased from 80℃ to 100℃, the moisture content decreased by only 0.002%, while the impact strength decreased by 6 J / m, indicating extremely limited improvement and significantly diminishing marginal benefits. Furthermore, high-temperature drying significantly increased energy costs and equipment heat load, and posed a risk of thermo-oxidative degradation of PP. In Comparative Examples 1-2 and 1-3, as the drying time increased from 4 hours to 6 hours and 8 hours, the moisture content decreased from 0.014% to 0.011% and 0.009%, respectively. However, the impact strength only increased from 680 J / m to 678 J / m and 676 J / m, remaining almost unchanged, indicating that there was no substantial gain after extending the drying time beyond 4 hours. Comparative Example 1-1 had a moisture content of 0.025% and an impact strength of 635 J / m. In Example 1-1, the moisture content was further reduced to 0.014%, and the impact strength increased to 680 J / m, an increase of approximately 7.1%. This shows that under the same drying temperature, further reduction in moisture content leads to a continuous increase in impact strength, demonstrating the direct impact of moisture content on impact performance. Comparative Example 1-4 had a moisture content as high as 0.045%, with an impact strength of only 645 J / m, indicating that when the temperature is too low, the internal moisture of PP cannot be fully removed within 4 hours, and the risk of hydrolysis still exists.
[0032] The function of step S2 is to premix PP-g-MAH with nano-silica, so that the maleic anhydride (MAH) polar groups on the PP-g-MAH molecular chain can chemically anchor and physically adsorb onto the silanol groups on the surface of nano-silica, forming PP-g-MAH / nano-silica hybrid particles. These hybrid particles act as molecular bridges between PP and nano-silica, allowing the rigidity-enhancing effect of nano-silica and the interfacial compatibilizing effect of PP-g-MAH to be superimposed, achieving uniform dispersion of the nanofiller in the PP matrix.
[0033] Specifically, the mass ratio of PP-g-MAH to nano-silica is 1:0.1-1:0.2; the mixing temperature is 180℃-200℃, the rotor speed is 60rpm-80rpm, and the mixing time is 3min-5min; the mass ratio of masterbatch to polypropylene homopolymer is 1:10-1:16; the mixing temperature is 190℃-210℃, the rotor speed is 80rpm-100rpm, and the mixing time is 3min-5min; the surface of the nano-silica is modified with a silane coupling agent.
[0034] Understandably, if nano-silica is directly blended with PP / EPR, skipping the S2 premixing step, the large specific surface area of nano-silica leads to high surface energy. This makes the nanoparticles highly susceptible to irreversible agglomeration in the melt, with agglomerate particle sizes reaching 5μm-20μm. These agglomerates become stress concentration points, ultimately reducing impact strength. The mass ratio of PP-g-MAH to nano-silica should be controlled within the range of 1:0.1-1:0.2: below 1:0.1, the MAH groups are insufficient to fully anchor the nano-silica surface, and some nanoparticles still agglomerate; above 1:0.2, excess PP-g-MAH itself has lower mechanical properties, and the molecular weight of the grafted polymer decreases, thus diluting the strength of the PP matrix.
[0035] In this embodiment, step S2 includes the following specific steps: Step S21: To verify the effect of the nano-silica dispersion method on the dispersed particle size and mechanical properties, different nano-silica addition methods were set up under the condition that the ratio of PP / EPR / PP-g-MAH / β nucleating agent remained unchanged: Method A (this invention): PP-g-MAH and nano-silica are first premixed to form a masterbatch, and then the masterbatch is mixed with PP homopolymer by intensive kneading; Method B (direct blending): Nano-silica is directly mixed with PP / EPR through internal mixing, without the PP-g-MAH premixing step; Method C (without PP-g-MAH premix): Nano silica is premixed with PP, but PP-g-MAH is not added; Method D (without nano silica): No nano silica is added; the remaining components and processes are exactly the same as in Method A.
[0036] Step S22: Take several groups of polypropylene homopolymer, 5 kg per group, and pre-treat them by drying under the optimized conditions determined in step S1. After cooling, seal and store for later use. Dry EPR simultaneously at 60℃ for 2 hours. Based on a typical formulation and using the total mass of the polypropylene homopolymer as a baseline: EPR 35%, β-nucleating agent 0.3%, antioxidant 0.7%, and lubricant 0.36%, weigh each component.
[0037] Method A: PP-g-MAH and nano-silica are added to an internal mixer at a mass ratio of 1:0.15 and mixed at 190℃ and 70rpm for 4 minutes to obtain masterbatch; then the masterbatch and PP homopolymer are added to an internal mixer at a mass ratio of 1:11 and mixed at 200℃ and 90rpm for 4 minutes to obtain mixture.
[0038] Method B: Add PP homopolymer, EPR, nano silica, PP-g-MAH, β nucleating agent, antioxidant, and lubricant into a mixer at once. The amount of PP-g-MAH is the same as in Method A. Mix at 200℃ and 90rpm for 8 minutes to obtain a mixture.
[0039] Method C: Premix nano-silica and PP homopolymer at 200℃ and 90rpm for 4min, then add EPR, PP-g-MAH, β-nucleating agent, antioxidant and lubricant, and continue to mix for 4min. The amount of PP-g-MAH is the same as in Method A, and a mixture is obtained.
[0040] Method D: Without adding nano-silica, PP homopolymer, EPR, PP-g-MAH, β nucleating agent, antioxidant, and lubricant are mixed in the same order as in Method A. The amount of PP-g-MAH is the same as in Method A, but it is not premixed with nano-silica. The total thermal history is consistent with Method A to eliminate the influence of processing thermal history on performance.
[0041] The mixtures obtained by the four methods are melt-extruded and granulated in step S4. The granules are dried at 80°C for 4 hours before use.
[0042] Table 2 shows the effects of different nano-silica dispersion methods on particle size and mechanical properties.
[0043] Table 2. Effects of different nano-silica dispersion methods on particle size and mechanical properties.
[0044] Table 2 Note: The equivalent circle diameter of nano-silica aggregates D50 was measured by TEM image analysis using JEOL JEM-2100F, accelerating voltage 200kV, ultrathin section 80nm, and 100 randomly selected particles; the equivalent circle diameter of EPR phase domains Dn was measured by SEM image analysis using FEI Nova Nano SEM 450, ruthenium tetroxide staining, secondary electron mode, accelerating voltage 5kV, and 50 randomly selected phase domains; the impact strength was determined according to GB / T 1843 using XJUD-5.5, 5.5J pendulum, and the flexural modulus was determined according to GB / T 9341; n=3 batches, 10 samples per batch, and the data were averaged.
[0045] As shown in Table 2, the nano-silica agglomerates of Example 2-1 have a D50 of only 0.18 μm, close to the size of native particles, an EPR phase domain size of 1.2 μm, an impact strength of 680 J / m, and a flexural modulus of 2300 MPa. All performance indicators are superior to other dispersion methods. Compared to Method D, Method A shows an increase of 135 J / m in impact strength and 150 MPa in flexural modulus, indicating that the nano-silica, under the dispersion method of this invention, simultaneously achieves both reinforcement and toughening effects. The uniformly dispersed nano-silica, on the one hand, provides a reinforcing effect as a rigid filler; on the other hand, by pinning at the PP-EPR phase interface, it refines the EPR phase domain and induces more crazes and shear bands as stress concentration points, absorbing impact energy. In Method B, the nano-silica is added directly without pre-dispersion, resulting in severe agglomeration due to its high surface energy, with a D50 reaching 8.5 μm and exceeding 20 μm in some cases. Compared to method D, the impact strength plummeted from 545 J / m to 520 J / m, indicating that the introduction of nano-silica actually worsened the impact toughness. Large agglomerates debonded from the PP matrix interface during impact, forming microcracks. These microcracks rapidly expanded into large cracks, leading to brittle fracture before the elastomer toughening mechanism was fully activated. Although the flexural modulus increased to 2420 MPa, the stiffness-toughness balance was severely disrupted. In method C, although the nano-silica was premixed with PP to partially depolymerize the agglomerates, the MAH groups could not effectively coat the nano-silica to form an anchoring layer because PP-g-MAH was added later and failed to pre-anchor the nanoparticle surface. Ultimately, the agglomerates remained as micron-sized clusters. Compared to method D, the impact strength increased slightly from 545 J / m to 580 J / m, a limited improvement, far less than the 135 J / m increase in method A, with a flexural modulus of 2370 MPa. This indicates that without MAH anchoring, the positive effects of nano-silica cannot be fully released.
[0046] In Method A, PP-g-MAH is first premixed with nano-silica. The polar groups of MAH preferentially adsorb onto the surface of the nano-silica through hydrogen bonds or chemical bonds, forming a "PP-g-MAH coating layer." This coating layer, on the one hand, utilizes the steric hindrance effect to inhibit secondary agglomeration of nanoparticles during subsequent processing; on the other hand, the long PP chains on the outer side of the coating layer have good compatibility with the PP matrix, allowing the nanoparticles to exist stably in the matrix in an "anchoring-dispersion" manner. Simultaneously, the uniformly dispersed nano-silica effectively pins the PP-EPR phase interface, refining the EPR phase domain from 2.5 μm in Method D to 1.2 μm, forming a toughened structure of nanoparticle pinning and elastomer stress dispersion. In Methods B and C, the agglomerated nanoparticles cannot form effective pinning at the phase interface, resulting in a coarse EPR phase domain, which prevents the toughening effect from being realized, leading to impact performance far lower than Method A.
[0047] Step S3 functions by pre-dispersing PP-g-MAH in the PP matrix, oriented the MAH groups toward the PP melt, and then adding EPR elastomer. This causes the polar MAH groups of PP-g-MAH to migrate interphase at the EPR / PP interface, migrating from the PP phase to the EPR / PP interface. At the interface, PP-g-MAH molecular bridges are formed, anchoring the PP chain segments at the MAH ends and physically entangled with the EPR at the carboxyl ends, thus achieving the interfacial compatibilization function of PP-g-MAH. Simultaneously, a β-nucleating agent is added in batches to induce the formation of β-crystals in the PP melt, achieving a dual-mechanism toughening effect of rubber based on both stress dispersion and β-crystal stress induction.
[0048] Specifically, the mixing temperature is 180℃-200℃, the β-nucleating agent is TMB-5 type β-nucleating agent or WBG series β-nucleating agent; the antioxidant includes a compound system of hindered phenolic antioxidants and phosphite antioxidants; the hindered phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the phosphite antioxidant is tris(2,4-di-tert-butylphenyl) phosphite; the mass ratio of the hindered phenolic antioxidant to the phosphite antioxidant is 1:1.5-1:2.5; based on the total mass of polypropylene homopolymer, the mass of ethylene-propylene rubber accounts for 35%, the mass of β-nucleating agent accounts for 0.3%, the mass of antioxidant accounts for 0.7%, and the mass of lubricant accounts for 0.36%.
[0049] Understandably, if the β-nucleating agent and EPR are added simultaneously, the β-nucleating agent is partially adsorbed by the EPR elastomer. Its solubility in the EPR phase is higher than that in PP, resulting in a reduced effective amount of β-nucleating agent entering the PP matrix, a decrease in β-crystal content, and a reduction in impact strength. If the PP-g-MAH dosage is less than 5%, the number of MAH groups is insufficient to adequately anchor the EPR / PP interface, leading to coarsening of the EPR phase domain size, insufficient interfacial adhesion, and limited impact strength. If it is greater than 10%, the low modulus of PP-g-MAH itself dilutes the strength of the PP matrix, and the flexural modulus decreases to <2100 MPa.
[0050] In this embodiment, step S3 includes the following specific steps: Step S31: To investigate the effect of PP-g-MAH content on EPR phase domain size, impact strength and flexural modulus, under the condition of keeping the PP / EPR / β nucleating agent / nano silica ratio constant, five parameter points of PP-g-MAH mass fraction are set based on the mass of polypropylene homopolymer: 3%, 5%, 8%, 10% and 13%. Step S32: Take several groups of polypropylene homopolymer pretreated under optimized conditions in step S1, 3 kg per group, and seal for later use; EPR is dried simultaneously at 60℃ for 2 hours and then sealed for later use. Based on the formula and the mass of polypropylene homopolymer, weigh each component as follows: EPR 35%, β nucleating agent 0.3%, antioxidant 0.7%, and lubricant 0.36%.
[0051] PP-g-MAH and nano-silica were added to a mixer at a mass ratio of 1:0.15 and mixed at 190℃ and 70rpm for 4 minutes to obtain a masterbatch. The masterbatch and polypropylene homopolymer were then added to a mixer at a mass ratio of 1:11 and mixed at 200℃ and 90rpm for 4 minutes to obtain a mixture.
[0052] The obtained mixture and EPR were fed into an internal mixer and mixed for 2 minutes. Then, β-nucleating agent was added in two equal batches with a 30-second interval. The mixture was then mixed for another 4 minutes. Antioxidant and lubricant were added, and the mixture was discharged after 1.5 minutes to obtain the modified mixture.
[0053] In step S33, the PP-g-MAH content is weighed according to the above five levels and the PP-g-MAH feeding amount is adjusted. The amount of nano silica is adjusted proportionally. The five modified mixtures are extruded and granulated according to step S4. The granules are dried at 80℃ for 4 hours and then tested.
[0054] Table 3 shows the effects of different PP-g-MAH contents on the phase domain size and mechanical properties of EPR.
[0055] Table 3. Effects of different PP-g-MAH contents on EPR phase domain size and mechanical properties
[0056] Table 3 Note: EPR phase domain Dn was analyzed by SEM image analysis using FEI Nova Nano SEM 450, liquid nitrogen brittle fracture + gold sputtering, secondary electron mode, 5kV, and 50 randomly selected phase domains were used to measure the equivalent circle diameter; impact strength was determined according to GB / T 1843, using XJUD-5.5, 5.5J pendulum; flexural modulus was determined according to GB / T 9341; β-PP content was calculated from DSC melt curves using a TA Q2000 differential scanning calorimeter, under N2 atmosphere protection, with a heating rate of 10℃ / min. Samples were heated from room temperature to 220℃ at 10℃ / min, and melt curves were recorded; n=3 batches, 10 samples per batch, and the average value was taken; the mass percentage of PP-g-MAH was 5%-10%, i.e., approximately 5.21%~9.09% calculated by rounding to the nearest integer, and the deviation between the endpoint values and the actual calculated values was within the industrial weighing error range.
[0057] Table 3 shows that when the PP-g-MAH content increases from 3% to 8%, the EPR phase domain refines from 4.2 μm to 1.2 μm, the impact strength at 23℃ increases from 420 J / m to 680 J / m, the impact strength at -20℃ increases from 280 J / m to 480 J / m, and the flexural modulus remains above 2300 MPa. When the content increases from 8% to 13%, the impact strength first increases to 695 J / m (10%) and then decreases to 665 J / m (13%), while the flexural modulus continues to decline. When the content reaches 13%, the EPR phase domain is further refined to 0.7 μm, and the β-PP content reaches 79%, but the flexural modulus drops sharply to 2080 MPa, which is lower than the general requirements for flexural modulus in the automotive structural parts field. When the PP-g-MAH content is low (3%), the number of MAH groups is insufficient, the surface coating of nano-silica is incomplete, the PP-EPR interfacial tension is high, and the EPR phase domain is coarsened (4.2 μm). Although the β-PP content reaches 76%, the interfacial area is small, the stress transfer efficiency is low, and the impact performance is poor. When the content increases to 5%-8%, the MAH groups undergo interphase migration at the EPR / PP interface, forming PP-g-MAH molecular bridges (MAH ends anchor PP segments, and carboxyl ends are entangled with EPR), the interfacial tension decreases, and the EPR phase domain is refined to 1.2 μm; at the same time, the dispersion uniformity of the β nucleating agent is improved, the β crystal toughening mechanism is fully activated, and the impact strength jumps to 680 J / m. When the content continues to increase to 10%-13%, the excess PP-g-MAH produces a dilution effect, the flexural modulus decreases, and the silver craze initiation efficiency decreases when the EPR phase domain is too small, resulting in a decrease in impact strength instead of an increase. This indicates that there is a suitable size range in the EPR phase domain, within which elastomer particles can effectively induce crazes and absorb impact energy.
[0058] The β-PP content was determined using a differential scanning calorimeter (DSC, TA Q2000) under nitrogen protection. 5-8 mg of sample was weighed, and the temperature was increased from room temperature to 220 °C at a rate of 10 °C / min, and the melting curve was recorded. The β-PP content (β-PP%) was calculated using the following formula: β-PP% = X β / (X) α +X β ), where X α and X β The values are the enthalpy of melting (J / g) for α-crystal and β-crystal, respectively. The melting peak temperature of α-crystal is approximately 165℃, and that of β-crystal is approximately 155℃. Three parallel samples were tested for each batch, and the average value was taken as the final result.
[0059] Table 4 shows the effects of different addition methods of β-nucleating agents on the β-PP content and mechanical properties.
[0060]
[0061] Table 4 Note: β-PP content was calculated from DSC melt curve; impact strength was determined according to GB / T 1843; EPR phase domain Dn was analyzed by SEM image analysis; flexural modulus was determined according to GB / T 9341; n=3 batches, 10 samples per batch, and the average value of the data was taken; the formulations of each group were the same as those in Example 2, only the method and timing of adding β nucleating agent were different.
[0062] Table 4 shows that Example 4-1 has a β-PP content of 80%, impact strengths of 680 J / m (23℃) and 480 J / m (-20℃), and an EPR phase domain of 1.2 μm, indicating superior overall performance. Comparative Example 4-1 shows a β-PP content of 58% added at the beginning of internal mixing, with impact strengths of 610 J / m and 410 J / m; Comparative Example 4-2 shows a β-PP content of 55% added after 6 minutes of internal mixing, with impact strengths of 585 J / m and 395 J / m. These data indicate that if the β-nucleating agent is added simultaneously with EPR at the beginning of internal mixing, some of it is adsorbed by the EPR phase, reducing the effective nucleating agent dosage entering the PP matrix and decreasing the β-PP content. If added later in the mixing process, the melt has already formed a stable two-phase structure, viscosity increases, and the nucleating agent becomes unevenly dispersed, further reducing the β-PP content to 55%. This invention selects to add the EPR in batches after mixing for 2 minutes. At this time, the EPR has been initially dispersed and the melt viscosity is moderate. Adding it in two batches avoids local over-concentration. This method has the following advantages: 1. Avoids excessive adsorption by the EPR phase; 2. Excellent dispersion uniformity; 3. Short high-temperature thermal history, β-PP content reaches 80%, and impact strength is 680J / m.
[0063] The function of step S4 is to ensure the stable existence of the β crystal form in the final product by using segmented temperature control and appropriate screw speed of the twin-screw extruder to prevent the β nucleating agent from thermally decomposing and recrystallizing at high temperatures while uniformly melting the modified mixture.
[0064] Specifically, the melt extrusion temperature is controlled in segments: feeding section 180℃-190℃, melting section 210℃-230℃, mixing section 230℃-250℃, die head 230℃-240℃, and screw speed 150rpm-250rpm.
[0065] Understandably, when the extrusion temperature exceeds 250℃, the TMB-5β nucleating agent undergoes thermal decomposition, resulting in a sharp decrease in the effective nucleating dose; when the screw speed is below 150rpm, the material stays in the barrel for too long, causing PP to undergo thermal oxidative degradation, increasing the carbonyl index, and decreasing the impact strength; when the speed is above 250rpm, the shear heat is too high, and at the same time, the material stays for too short a time, resulting in uneven mixing.
[0066] In this embodiment, step S4 includes the following specific steps: In step S41, under the condition of a fixed formula and a constant screw speed of 200 rpm, the mixing section temperature is set to four levels: 210℃, 230℃, 250℃, and 270℃. The temperatures of the feeding section, melting section, and die head are adjusted in conjunction with the mixing section, and the temperature difference between each section remains constant.
[0067] Step S42: Take 5 groups of polypropylene homopolymer pretreated under the optimized conditions of step S1, 5 kg per group, and seal for later use; EPR is simultaneously dried at 60℃ for 2 hours. Based on the formula and the mass of the polypropylene homopolymer: EPR 35%, β-nucleating agent 0.3%, antioxidant 0.7%, and lubricant 0.36%, weigh each component. Prepare PP-g-MAH / nano silica masterbatch according to the optimized process of step S2 and mix it with the PP homopolymer to obtain a mixture; according to the optimized process of step S3, with PP-g-MAH content of 8%, after intensive mixing for 2 minutes, add the β-nucleating agent in batches to obtain the modified mixture.
[0068] In step S43, the modified mixture is melt-extruded and granulated under different extrusion temperatures, with the screw speed fixed at 200 rpm. After the extruded strip is cooled in a water bath and granulated by a pelletizer, the granules are dried at 80°C for 4 hours for later use.
[0069] Table 5 shows the data on the effects of different extrusion temperatures on β crystal content and impact strength.
[0070] Table 5. Effect of different extrusion temperatures on β-crystal content and impact strength
[0071] Table 5 Note: β-PP content was calculated from DSC melt curve, TA Q2000, heating rate 10℃ / min, N2 atmosphere; impact strength was determined according to GB / T 1843, XJUD-5.5, 5.5J pendulum; MFR was determined according to GB / T 3682.1; n=3 batches, 10 samples per batch, and the average value of the data was taken.
[0072] As shown in Table 5, in Comparative Example 5-1, the extrusion temperature was low, resulting in high PP melt viscosity. Although the β-PP content reached 80%, the shear stress was insufficient to effectively refine the EPR phase domain, leading to uneven dispersion of nano-silica and an impact strength of only 541 J / m. In Example 5-1, the temperature was increased to 230℃, reducing melt viscosity and increasing shear stress. This effectively broke down and refined the EPR phase domain, improved nano-silica dispersion, and increased the impact strength to 623 J / m. In Example 5-2, the temperature was further increased to 250℃, further reducing melt viscosity. This facilitated the refinement of the EPR phase domain and the uniform dispersion of nano-silica. Simultaneously, the β-PP content remained high at 82%, fully activating β-crystal toughening and achieving an impact strength of 685 J / m. In Comparative Example 5-2, the temperature exceeded the thermal decomposition temperature of TMB-5 by approximately 260°C. The decomposition of the β-nucleating agent caused β-PP to drop sharply to 25%, while PP underwent thermo-oxidative degradation, causing the MFR to rise to 4.2 g / 10 min and the impact strength to drop sharply to 442 J / m.
[0073] Examples and Comparative Examples The specifications of the raw materials used in the following examples are as follows: Polypropylene homopolymer: melt flow rate (MFR, 230℃ / 2.16kg) is 2.5g / 10min-3.5g / 10min; Ethylene-propylene rubber (EPR): Ethylene content 65%-75%, Mooney viscosity ML(1+4) 125℃ is 50-70; PP-g-MAH: Grafting rate 0.8%-1.2%, MAH content 0.5%-0.8wt%, melt flow rate (190℃ / 2.16kg) 15g / 10min-30g / 10min; Nano-silica: native particle size 10nm-30nm, specific surface area 200±20m² 2 / g, the surface is modified by γ-aminopropyltriethoxysilane (KH550). The modification method is as follows: disperse nano-silica in anhydrous ethanol, add KH550, the amount of which is 3%-5% of the mass of nano-silica, reflux at 80℃ for 4h, filter, wash and dry for later use. β-nucleating agent: TMB-5 type; Antioxidant 1010 and Antioxidant 168; Lubricant: calcium stearate.
[0074] Example 1 The lower limit parameters are used for each processing step: S2 premixing: PP-g-MAH and nano silica are mixed at a ratio of 1:0.1; S3: mixing temperature is 180℃, and β nucleating agent is added in the second minute of mixing; S4: extrusion mixing section is 230℃, and screw speed is 200rpm.
[0075] Results: Impact strength 540 J / m at 23℃, 370 J / m at -20℃, flexural modulus 2350 MPa, β-PP content 77%, MFR 1.8 g / 10 min.
[0076] Example 2 The median parameters were used for each processing step: S2: PP-g-MAH and nano silica were mixed at a ratio of 1:0.15; S3: the mixing temperature was 190℃, and the β nucleating agent was added in the second minute of mixing; S4: the extrusion mixing section was 240℃, and the screw speed was 200rpm.
[0077] Results: Impact strength 680 J / m at 23℃, 480 J / m at -20℃, flexural modulus 2300 MPa, β-PP content 80%, MFR 2.1 g / 10 min, tensile strength 24.5 MPa, elongation at break 185%.
[0078] Example 3 Each processing step uses the upper limit parameters: S2: PP-g-MAH and nano silica are mixed at a ratio of 1:0.2; S3: mixing temperature is 200℃, and the β nucleating agent is added in the second minute of mixing; S4: extrusion mixing section is 250℃, and the screw speed is 200rpm.
[0079] Results: Impact strength: 665 J / m at 23℃, 465 J / m at -20℃; flexural modulus: 2280 MPa; β-PP content: 80%; MFR: 2.4 g / 10 min. Compared with Example 2, under the condition of keeping the EPR content unchanged, the impact strength and flexural modulus of Example 3 decreased slightly, but still remained at a high level, verifying the robustness of the overall performance of the composition within the process parameter range of the present invention.
[0080] Comparative Example 1 Using the same treatment as in Example 2, S2: skip the PP-g-MAH / nano silica premixing step and directly blend the nano silica with PP / EPR.
[0081] Results: The EPR phase domain was coarsened to 2.8 μm, with an impact strength of 520 J / m (23℃) and 365 J / m (-20℃), a nano-silica agglomerate D50 of 8.5 μm, and a flexural modulus of 2420 MPa. These results demonstrate that the core contribution of the S2 premixing step lies in refining the EPR phase domain and enhancing interfacial adhesion.
[0082] Comparative Example 2 The same treatment as in Example 2 was used, but the β nucleating agent was omitted.
[0083] Results: β-PP=0%, impact strength 480 J / m (23℃) and 335 J / m (-20℃), flexural modulus 2380 MPa. Compared with Example 2 of this invention, the impact strength decreased by 29.4% at 23℃ and by 30.2% at -20℃, verifying the key role of the β-nucleating agent in improving impact resistance at room temperature and low temperature. Based on the good dispersion of PP-g-MAH / nano silica premix, the introduction of the β-nucleating agent contributed an additional 200 J / m to the improvement in impact strength.
[0084] Comparative Example 3 The same treatment as in Example 2 was used, but with EPR as the sole toughening agent, without PP-g-MAH or β-nucleating agent.
[0085] Results: Impact strength 450 J / m (23℃), flexural modulus 1850 MPa. To achieve the impact strength level of this invention, the EPR needs to be increased to over 38%, at which point the flexural modulus will further decrease to below 1700 MPa, failing to meet the rigidity requirements of automotive structural components. This verifies the significant contribution of the three-component route of elastomer + β-nucleating agent + PP-g-MAH in this invention.
[0086] Comparative Example 4 The same treatment as in Example 2 was used, but with a higher dosage of 38% EPR.
[0087] Results: The impact strength at 23℃ was 720 J / m, but the flexural modulus dropped significantly to 1920 MPa, and the MFR was 3.8 g / 10 min. The overall performance was inferior to that of Example 2 of the present invention. This verifies the rationality of the parameter range of the present invention. Through the synergy of β nucleating agent and PP-g-MAH, higher impact strength is achieved at a lower EPR dosage while maintaining a high flexural modulus.
[0088] Overall beneficial effects analysis results To comprehensively evaluate the overall performance of the technical solutions of this invention, Example 2 of this invention was used as the test group, and Comparative Examples 1-4 were used as the control group. Five indicators, namely simply supported beam impact test, universal material test, DSC, SEM and TEM, were used to comprehensively evaluate the differences in the effects of each technical solution.
[0089] Table 6. Comparison of Overall Beneficial Effects Data
[0090] Table 6 Notes: Impact strength: XJUD-5.5, GB / T 1843, n=3 batches, 10 specimens per batch; Flexural modulus: Instron 5967, GB / T 9341, n=3 batches; β-PP content: DSC method, TA Q2000, n=3 batches; EPR phase domain: SEM image analysis, FEI Nova Nano SEM 450, n=3 batches; Nano silica dispersion: TEM, JEOL JEM-2100F, n=3 batches; Tensile strength: Instron 5967, GB / T 1040.2, n=3 batches; MFR: XRZ-400, 230℃ / 2.16kg, n=3 batches. Data are expressed as mean.
[0091] Explanation of the overall beneficial effects I. Principle of Component Synergy The composition of the present invention comprises four types of core modified components, and there is a synergistic effect among the components.
[0092] PP-g-MAH compatibilizer + EPR elastomer: One end of the PP-g-MAH molecular chain is a PP segment, and the other end is a MAH polar group, forming a PP-PP-g-MAH-EPR three-phase interfacial bridging structure. The interphase migration effect of the MAH group at the EPR / PP interface causes PP-g-MAH to be preferentially distributed in the interfacial layer, significantly enhancing the interfacial bonding strength. This allows the EPR phase domain to effectively transfer stress during impact, stimulating the formation of numerous crazes and shear bands, and greatly improving the impact energy dissipation efficiency.
[0093] β-nucleating agent + PP matrix: The symmetrical triamide structure of the TMB-5 molecule acts as a heterogeneous nucleation site for the β-crystalline form during the cooling process of the PP melt, inducing the PP molecular chains to stack in the β-crystalline form. The lamellar structure of β-PP is more loose than that of α-PP, with lower resistance to interlamellar slippage, making it more prone to lamellar slippage and torsion under impact loads, thus dissipating more impact energy. At the same time, due to its looser lamellar structure, the β-crystalline form exhibits less stress concentration under the same stress conditions compared to the α-crystalline form, which is beneficial for delaying the occurrence of brittle fracture.
[0094] Nano-silica + PP-g-MAH: The MAH polar groups of PP-g-MAH form hydrogen bonds and chemical anchors with the Si-OH on the surface of nano-silica, causing the nano-silica to be encapsulated by PP-g-MAH molecular chains. These hybrid particles are uniformly dispersed in the PP matrix. Under impact load, the nanoparticles act as stress concentration points, inducing a large number of microcracks, while simultaneously restricting the relaxation of the PP molecular chains, thus achieving a simultaneous improvement in rigidity and toughness.
[0095] EPR elastomer + β nucleating agent: The EPR rubber phase disperses impact energy through stress concentration effect; the β nucleating agent dissipates impact energy through stress-induced lamellar slip. The two mechanisms work together to improve impact toughness through different pathways.
[0096] II. Principle of Process Synergy S2→S3→S4 forms a complete process chain from PP-g-MAH / nano premix to elastomer incorporation to extrusion granulation, with close material transfer and structural evolution relationships between each step.
[0097] S2 provides the PP-g-MAH-anchored nano-silica dispersion basis for S3: S2 premixing pre-anchors the MAH groups of PP-g-MAH to the nano-silica surface, forming stable hybrid particles. After the addition of EPR in S3, these hybrid particles simultaneously contact the PP matrix and the EPR phase domain, further strengthening the three-dimensional network structure of the EPR / PP interface, and confining the EPR phase domain within a finer size range.
[0098] S3 provides the optimal microstructure for S4: the PP-g-MAH compatibilizer in S3 refines the EPR phase domain to 1.2 μm, while the introduction of the β nucleating agent results in 80% β crystal form in the PP matrix. This microstructure is oriented and fixed by melt flow during the S4 extrusion granulation process, and is maintained in the final product.
[0099] S4's temperature control strategy ensures the stability of the β crystal form: the temperature of the extrusion mixing section is controlled at 230℃-250℃, which ensures that PP is completely melted and avoids the thermal decomposition of TMB-5 and β→α recrystallization. After the extruded strip is cooled in a water tank and granulated, the β-PP content is ≥75%.
[0100] The technical solution of the present invention has been described above with reference to the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a high-impact polypropylene resin composition, characterized in that, Includes the following steps: Step S1: The polypropylene homopolymer and ethylene-propylene rubber (EPR) are dried under preset conditions to obtain pretreated raw materials for later use. Step S2: PP-g-MAH and nano silica are fed into an internal mixer in a preset ratio to obtain PP-g-MAH / nano silica masterbatch. Then, the masterbatch and the polypropylene homopolymer pretreatment raw material are fed into the internal mixer in a preset ratio to control the mass of PP-g-MAH to account for 5%-10% of the total mass of polypropylene homopolymer, and a mixture is obtained. Step S3: The mixture and ethylene-propylene rubber are fed into a mixer in a preset ratio; after mixing for 2 minutes, the β nucleating agent is added in two equal batches with a 30-second interval between the two batches. After mixing for another 3-6 minutes, the antioxidant and lubricant in a preset ratio are added. The mixture is then discharged after 1-2 minutes to obtain the modified mixture. Step S4: The modified mixture is transferred to a twin-screw extruder for melt extrusion granulation, cooled in a water bath, pelletized and dried, and then cooled to room temperature to obtain high-impact polypropylene resin composition granules.
2. The method for preparing the high-impact polypropylene resin composition according to claim 1, characterized in that, In step S1, the preset drying conditions are as follows: polypropylene homopolymer is dried at 80℃-100℃ for 4 hours to achieve a moisture content of ≤0.02%; ethylene-propylene rubber is dried at 60℃-80℃ for 2 hours.
3. The method for preparing the high-impact polypropylene resin composition according to claim 2, characterized in that, In step S2, the mass ratio of PP-g-MAH to nano-silica is 1:0.1-1:0.2; the mixing temperature is 180℃-200℃; the rotor speed is 60rpm-80rpm; and the mixing time is 3min-5min.
4. The method for preparing the high-impact polypropylene resin composition according to claim 3, characterized in that, In step S2, the mass ratio of the masterbatch to the polypropylene homopolymer is 1:10-1:16; the mixing temperature is 190℃-210℃; the rotor speed is 80rpm-100rpm; and the mixing time is 3min-5min.
5. The method for preparing the high-impact polypropylene resin composition according to claim 4, characterized in that, In step S2, the surface of the nano-silica is modified with a silane coupling agent.
6. The method for preparing the high-impact polypropylene resin composition according to claim 5, characterized in that, In step S3, the mixing temperature is 180℃-200℃, and the β-nucleating agent is TMB-5 type β-nucleating agent or WBG series β-nucleating agent.
7. The method for preparing the high-impact polypropylene resin composition according to claim 6, characterized in that, In step S3, the antioxidant comprises a compound system of hindered phenolic antioxidants and phosphite antioxidants; the hindered phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the phosphite antioxidant is tris(2,4-di-tert-butylphenyl)phosphite; the mass ratio of the hindered phenolic antioxidant to the phosphite antioxidant is 1:1.5-1:2.
5.
8. The method for preparing the high-impact polypropylene resin composition according to claim 7, characterized in that, In step S3, based on the total mass of polypropylene homopolymer, the mass of ethylene-propylene rubber accounts for 35%, the mass of β nucleating agent accounts for 0.3%, the mass of antioxidant accounts for 0.7%, and the mass of lubricant accounts for 0.36%.
9. The method for preparing the high-impact polypropylene resin composition according to claim 8, characterized in that, In step S4, the melt extrusion temperature is controlled in segments: feeding section 180℃-190℃, melting section 210℃-230℃, mixing section 230℃-250℃, die head 230℃-240℃, and screw speed 150rpm-250rpm.
10. A high-impact polypropylene resin composition prepared by the preparation method according to any one of claims 1-9, characterized in that, Based on the mass of the polypropylene homopolymer, the mass percentage of each raw material component is as follows: The composition consists of 100% polypropylene homopolymer, 35% ethylene-propylene rubber, 0.3% β-nucleating agent, 0.7% compounded antioxidant, 0.36% lubricant, 5%-10% PP-g-MAH, and 0.5%-2.0% nano-silica.